Does the Middle East and North Africa Region Experience 'Conflict Traps'? - Lind, Lene (World Bank, Washington, DC, 2012)
The 2011 World Development Report (WDR) on 'Conflict, Security and Development' has reaffirmed global research that conflict is in many respects a self-perpetuating cycle. Put simply, factors related to the onset of conflict are reinforced by ensuing violence trapping countries in a cycle which is hard to break, with ominous implications for development assistance. The best known exposition of the conflict trap is based on economic factors. Collier et al. wrote in 2003 that a 'country that first falls into the trap may have a risk of new war that is 10 times higher just after that war has ended than before the war started. If the country succeeds in maintaining post-conflict peace for ten years or so, the risk is considerably reduced, but remains at a higher level than before the conflict'. According to this 2003 study, war not only erodes and complicates economic conditions, it also allows particular groups to accumulate wealth and, hence, gain a financial stake in continued or renewed violence. As the 2011 WDR itself suggests, some of the most integral drivers of conflict and fragility may relate to institutions and the quality of governance.